Neonatal Extracorporeal Membrane Oxygenation Due to Respiratory Failure: A Single Center Experience Over 28 Years - Reiterer, Friedrich; Resch, Elisabeth; Haim, Michaela; Maurer-Fellbaum, Ute; Riccabona, Michael; Zobel, Gerfried; Urlesberger, Berndt; Resch, Bernhard (Frontiers in Pediatrics, 2018)
ECMO therapy is worldwide declining; hence, its therapeutic use is questioned. We aimed to report our experience with neonatal ECMO due to respiratory failure over a 28 year time period. This is a retrospective single center observational study including all neonates admitted to ECMO due to respiratory failure between 1989 and 2016 at Graz, Austria. Data were collected regarding survival rate, duration of ECMO, complications, length of hospital stay, changes over time, and follow-up. Sixty-seven neonates were admitted and 43 (64%) needed ECMO - median birth weight 3390 grams (range 1810 – 4150) and gestational age 39 weeks (32 – 43). Survival rate was 65% (28/43); with higher rates in meconium aspiration syndrome (MAS) 89% vs. congenital diaphragmatic hernia (CDH) 46% and septic shock 44% (p=0.005 and p=0.006, respectively). ECMO duration was median 5 days (1-30) and veno-arterial ECMO (52%) dominated. Need for ECMO therapy decreased over time (p<0.001). Complications occurred in 31 (72%) neonates. Five neonates had cerebral hemorrhages (11.4%) and four had cerebral infarction (9.1%). Of 26 survivors 17 (65%) showed normal neurodevelopmental outcome at median follow-up of 73 months. Motor deficits were present in one case, cognitive deficits in 9 (35%). Median length of hospital stay was 78 days in those with deficits and 29 in those with normal neurodevelopmental outcome (p<0.001). In conclusion, survival rate did not change over the study time but indications for ECMO. Cognitive impairment was the major long-term deficit following neonatal ECMO being associated with longer hospital stay.